The Convergence of Factors That Affect the Dairy Product Market: A Comparative Analysis of European Union Countries - Jurij Klapkiv; Petro Putsenteilo; Vitalii Karpenko (Comparative Economic Research, 2023)
The European Union is a large producer of milk and dairy products. It is also a significant market for the consumption of dairy products, which is characterised by effective demand, and it significantly influences the markets of other food products. The main milk producers in the EU are Germany, France, Poland, the Netherlands, Italy and Spain. Intensive migration has contributed to additional demand for food products, in particular, dairy products. This provided the basis for the construction and calculation of a dynamic model of dairy production, the export of dairy products, and the coexistence with the existing population as the main consumers in the EU–27 countries and Great Britain between 2004 and 2020.